From imperialism to inpatient care: Work differences of Filipino and White registered nurses in the United States and implications for COVID‐19 through an intersectional lens. Issue 4 (16th April 2021) - Nazareno, Jennifer; Yoshioka, Emily; Adia, Alexander C; Restar, Arjee; Operario, Don; Choy, Catherine Ceniza
Abstract: In the United States, nursing is the largest healthcare profession, with over 3.2 million registered nurses (RNs) nationwide and comprised of mostly women. Foreign‐trained RNs make up 15 percent of the RN workforce. For over half a century, the U.S. healthcare industry has recruited these RNs in response to nurse shortages in hospitals and nursing homes. Philippines‐trained RNs make up 1 out of 20 RNs in this country and continue to be the largest group of foreign‐trained nurses today. Recently, the news media has publicized the many deaths of Filipino RNs as a result of the COVID‐19 pandemic in the United States. Given the imperial historical ties between these two countries in the context of the nursing profession and the enduring labor inequities that persist, this nationally representative study is one of the few to our knowledge to not only quantitatively examine the current work differences in characteristics and experiences of Philippines‐trained RNs and U.S.‐trained white RNs practicing in the United States today, but to also do so from an intersectionality lens. The overall aim of this paper is to illuminate how these differences may serve as potential factors contributing to the disproportionate number of Filipino nurses' COVID‐19 related vulnerability and deaths in the workplace.